tidal ventilation model for oxygenation in respiratory failure - Whiteley, J; Farmery, A; Gavaghan, D; Hahn, C (2003)
We develop tidal-ventilation pulmonary gas-exchange equations that allow pulmonary shunt to have different values during expiration and inspiration, in accordance with lung collapse and recruitment during lung dysfunction [Am. J. Respir. Crit. Care Med. 158 (1998) 1636]. Their solutions are tested against published animal data from intravascular oxygen tension and saturation sensors. These equations provide one explanation for (i) observed physiological phenomena, such as within-breath fluctuations in arterial oxygen saturation and blood-gas tension; and (ii) conventional (time averaged) blood-gas sample ox